2006
DOI: 10.1007/s00709-006-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin concentrates at the apex of growing hyphae and localizes to the Spitzenkörper in Aspergillus nidulans

Abstract: The calmodulin (CaM) localization pattern in the growing hyphal tip of Aspergillus nidulans was studied with the functional GFP::CaM fusion protein. A faint tip-high gradient of CaM was found in the growing hyphal tip, with CaM highly localized in the region corresponding to the Spitzenkörper forming a bright granule. The position of highly concentrated CaM in the extreme apex seemed to determine the orientation of the hypha. The normal pattern of CaM localization was also shown to be dependent on the integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
2
17
0
2
Order By: Relevance
“…MM, YAG, YG (YAG without agar), YUU, YUUK, MMGPR, and MMGTPR (MMGPR with 100 mM threonine) media have been described in previous works (38)(39)(40). Growth conditions, crosses, and induction conditions for alcA(p)-driven expression were the same as those described previously (41). Expression of tagged genes under the control of the alcA promoter was regulated by different carbon sources, with repression on glucose, derepression on glycerol, and induction on threonine.…”
Section: Methodsmentioning
confidence: 99%
“…MM, YAG, YG (YAG without agar), YUU, YUUK, MMGPR, and MMGTPR (MMGPR with 100 mM threonine) media have been described in previous works (38)(39)(40). Growth conditions, crosses, and induction conditions for alcA(p)-driven expression were the same as those described previously (41). Expression of tagged genes under the control of the alcA promoter was regulated by different carbon sources, with repression on glucose, derepression on glycerol, and induction on threonine.…”
Section: Methodsmentioning
confidence: 99%
“…For solid media, 2 % agar was added. Growth conditions, crosses and induction conditions for alcA(p)-driven expression were as previously described (Wang et al, 2006). Transformation was done according to a method described elsewhere (May, 1989;Osmani et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…In fungi, CaM is required for hyphal growth, morphogenesis, germination, and penetration into plant tissue (Ahn and Suh 2007;Ahn et al 2003;Sato et al 2004;Wang et al 2006). In our previous study, we found that CaM gene expression is regulated in parallel with genes encoding most isozymes of LiP and MnP in P. chrysosporium (Minami et al 2007(Minami et al , 2009.…”
Section: Introductionmentioning
confidence: 99%